Blue light stimulation of the blind spot in human: from melanopsin to clinically relevant biomarkers of myopia - Amorim-de-Sousa, Ana; Chakraborty, Ranjay; Collins, Michael J.; Fernandes, Paulo; González‑Méijome, José; Hannibal, Jens; Hoseini-Yazdi, Hosein; Read, Scott A.; Ellrich, Jens; Schilling, Tim (Bioelectronic Medicine, 2024)
The protective effects of time spent outdoors emphasize the major role of daylight in myopia. Based on the pathophysiology of myopia, the impact of blue light stimulation on the signaling cascade, from melanopsin at the blind spot to clinically relevant biomarkers for myopia, was investigated. Parameters and site of light stimulation are mainly defined by the photopigment melanopsin, that is sensitive to blue light with a peak wavelength of 480 nm and localized on the intrinsically photosensitive retinal ganglion cells (ipRGC) whose axons converge to the optic disc, corresponding to the physiological blind spot. Blue light at the blind spot (BluSpot) stimulation provides the opportunity to activate the vast majority of ipRGC and avoids additional involvement of rods and cones which may exert incalculable effects on the signaling cascade. Experimental studies have applied anatomical, histochemical, electrophysiological, imaging, and psychophysical methods to unravel the mode of action of BluSpot stimulation. Results indicate activation of melanopsin, improvement of contrast sensitivity, gain in electrical retinal activity, and increase of choroidal thickness following BluSpot stimulation. Short-term changes of clinically relevant biomarkers lead to the hypothesis that BluSpot stimulation may exert antimyopic effects with long-term application.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Axial length; Choroidal thickness; Contrast sensitivity; Dopamine; Electroretinogram; Ganglion cells; Nearsightedness; Optic disc; Pupil response; Retina